2020
DOI: 10.11591/ijece.v10i5.pp4973-4981
|View full text |Cite
|
Sign up to set email alerts
|

Modelling turn away intention of information technology professionals in Bangladesh: a partial least squares approach

Abstract: Despite, Bangladesh produces many IT graduates each year but only one tenth of total graduates contribute in IT development sector. In order to keep the contribution to economy through IT development, it is crucial for IT industry to know the factors that influence turn away of IT graduates. In this paper, building upon role stress theory, we develop a research model to explore the influence of workplace exhaustion and threat of professional obsolescence (TPO). Data were gathered from 185 IT professionals from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 28 publications
(48 reference statements)
0
4
0
Order By: Relevance
“…Smart partial least square (PLS) has been used to analyze the current study based on the understanding that it is an alternate of ordinary least square regression and applies partial least square path modeling. Scholars considered it suitable for the studies examining causal associations with hypothesis testing (Arman et al, 2020;Mansoor and Noor, 2019). Thus, to test the hypothesized paths and check for the results of the direct and mediation paths, the authors of the current study applied structural equation modelling through SMART PLS 3 (Yuan et al, 2020).…”
Section: Control Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…Smart partial least square (PLS) has been used to analyze the current study based on the understanding that it is an alternate of ordinary least square regression and applies partial least square path modeling. Scholars considered it suitable for the studies examining causal associations with hypothesis testing (Arman et al, 2020;Mansoor and Noor, 2019). Thus, to test the hypothesized paths and check for the results of the direct and mediation paths, the authors of the current study applied structural equation modelling through SMART PLS 3 (Yuan et al, 2020).…”
Section: Control Variablesmentioning
confidence: 99%
“…Thus, to test the hypothesized paths and check for the results of the direct and mediation paths, the authors of the current study applied structural equation modelling through SMART PLS 3 (Yuan et al, 2020). Serval recent studies applied this software and data analysis technique to assess the theoretical foundations of the constructs (Noor et al, 2021;Arman et al, 2020).…”
Section: Control Variablesmentioning
confidence: 99%
“…The IS literature has found that the work exhaustion dimension of burnout positively influences turnover intention (e.g. Ahuja et al, 2007;Ford et al, 2013;Moore, 2000) and turnaway intention (Arman et al, 2020;Armstrong et al, 2015). While exhaustion has been most often used as a proxy for burnout, cynicism is a powerful predictor of turnover intention (Leiter and Maslach, 2009).…”
Section: Turnover and Turnaway Intentionmentioning
confidence: 99%
“…SEM is a comprehensive statistical method that examines relationships between observed and latent factors [12]. It has been widely used in confirmatory factory analysis in many topics and fields [13]- [15].…”
Section: Introductionmentioning
confidence: 99%